PERTUMBUHAN DAN HASIL GALUR-GALUR F4 PADI RAWA PADA RAWA LEBAK - Sumardi Sumardi; M. Chozin; Hermansyah Hermansyah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[GROWTH AND YIELD OF F4 SWAMP RICE LINES ON LINE SWAMP]. Growth and yield of swamp rice are depending on the plant ability to adapt in swampy agro-ecosystem which characterized by several limiting factors. This study was addressed to evaluate the growth and yield characteristics of six lines of swamp rice bred for the development of high-yielding rice varieties best suited for swamp land production. Evaluation was conducted in a pot experiment using UBPR2, UBPR3,UBPR6, UBPR7, UBPR9, and UBPR10 as planting materials. These lines were the F4 generation derived from crosses involving local Bengkulu swamp rice varieties. Observations were made on 13 plant characteristics, dry matter accumulation,  leaf area ratio, specific leaf weight, net assimilation rate, plant height, productive tiller number, heading date, maturity date, panicle length, grain number per panicle, percent of filled grain, and plant yield (the grain weight per clump).  The collected data were subjected to analysis of variance and least significant difference test at 5% level.  Results indicated that all lines physiologically exhibited similar growth patterns, excepting the capability of accumulating dry matter at 40 dap. In this case, UBPR6 produced the highest dry matter accumulation (24.34 g). Based on the morphological performances, significant variations among the lines were observed on most of the observed characteristics, except on productive tiller number and panicle length UBPR10 was the line produced the tallest plant stature (160.72 cm), UBPR2 was the earliest flowering and maturing line (76,33 and 111 dap), whereas UBPR6 was the line produced the highest grain number per panicle (212,2), percent of filled grain (95%),  and plant yield (82.50 g per clump).